(3GdQSGdI GdehSheI HQSGdI GdfSGA GdcHjQIs ((3GdCejQ YjSi GdJfhNi s)
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe HSe Gddg GdQMef GdQMje MOhO YHOg GdEeGe SHMGfg ef CXgQ MceJg aCYLR HQjJg s
(3BNQgG (B:s
(3hEfeG bUO HPdc Ydi jOi QabkG Hef EJUd Edjg hLdGdg dge hTQakG hYRkG hGdMeO hGdTcQ ddehdi hMOg dGTQjc dg hHg CSJYjf ai cd GdCehQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds